Game-Based Learning Innovation to Development of Analytical Thinking Ability - Gowithayakorn, Thasanai (ASEAN Journal of Education, 2023)
As global trends have changed, the pattern of game-playing has adapted. It is transitioning from single-player or multiple player game and playing with friends or indeed strangers. The opportunity exists to leverage educational innovation to harness game-play in a constructive curriculum grounded manner through “Game-Based Learning”. This, through various simulations, encourages students to play and learn simultaneously. Critically, this will not only create a new learning environment grounded in academic principles and curricula but facilitate learners honing more important analytical skills which are the bedrock of all forms of advanced thinking. In employing such a pedagogical approach, teachers in designing game-based learning are advised to gain a clear understanding of its characteristics before applying it to the teaching curriculum. Two evident alternatives exist, bespoke games designed by the teacher and learning games already available. In building a learning game, teachers should be mindful to give explicit attention to the learning goals and outcomes sought in developing such games to enhance the benefits to students and thus engender a positive and efficient learning conjunct to traditional teaching methods.